2020
DOI: 10.1088/2057-1976/ab90a0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous reconstruction of absorption, scattering and anisotropy factor distributions in quantitative photoacoustic tomography

Abstract: We present for the first time the simultaneous reconstruction of three optical parameters distributions of biological tissues namely, the absorption µ a and scattering µ s coefficients, as well as the anisotropy factor g of the Henyey-Greenstein phase function as a new optical contrast. The 2D images are obtained from the simulation experiments and multi-source quantitative photoacoustic tomography with the radiative transfer equation (RTE) as light transport model. The image reconstruction method is based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The objective function J (39) will be minimized by means of the inverse algorithm when Eq. ( 42) is satisfied [34,35].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The objective function J (39) will be minimized by means of the inverse algorithm when Eq. ( 42) is satisfied [34,35].…”
Section: Discussionmentioning
confidence: 96%
“…A gradient-based optimization algorithm using the quasi-Newton method with Lm-BFGS [34,35,38] was used to iteratively minimize the objective function J given by Eq. ( 16).…”
Section: Inverse Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“… 141 , it was shown that the nonuniqueness can be overcome using multiple optical illuminations to obtain more data. One way to achieve this would be by illuminating the target from different directions 141 , 143 , 150 , 162 168 or using light patterns. 169 This approach has not yet been exploited experimentally, perhaps because experimentalists are concerned to obtain the maximum signal possible given the weakness of the photoacoustic effect, and so try to flood the tissue with light from as many directions as possible.…”
Section: Photoacoustic Inverse Problemsmentioning
confidence: 99%